Molal volume and compressibility of aqueous non-electrolyte solutions - JUSZKIEWICZ, Adam (Archives of Acoustics, 2015)
The measurements of ultrasonic velocity and of density in aqueous solutions of 20 non-electrolytes were carried out. From the obtained results isentropic compressibility, apparent molal volumes and apparent molal compressibilities were calculated. The changes of these parameters with the change of concentration of the non-electrolytes confirm the model of hydration of non-electrolytes suggested previously on the basis of ultrasonic velocity measurements in binary and ternary systems.